Management of patients intoxicated with psychotropic drugs attended va new admission nurses - Machado Arango, Vilma; Ortega Dugrot , Yanet; Gener Villarpanda, Carmen Odalys; González Barrero , Marylú; Suárez Oceguera, Julieth; Solís Solís, Susana (International Journal of Neurology, 2025)
Introduction: Poisoning is a preventable public health problem that affects the world population. In Cuba, the level of consumption was negligible; but the coincidence of economic and social factors favored the premises for the increase. In response, institutional tools were implemented, such as the National Drug Prevention Program for Adolescents and Young People. This research has as objective: to characterize the management of the patient intoxicated by psychotropic drugs directed to the nursing staff of new admission in the medical emergency services of the Clinical Surgical Teaching Hospital “Julio trigo López”. Methods: an observational, descriptive, cross-sectional study was conducted. In the period from January 2021 to March 2022. The universe was made up of 80 nurses who worked in the medical emergency services of the Julio Trigo López clinical surgical hospital of the Arroyo Naranjo municipality. Results: the need for learning related to the topic of acute poisoning was identified, which has an impact on professional training, from the scientific, human, with a transformative character, that responds to social needs. Conclusions: The management of the intoxicated patient was characterized. A training course on the management of the patient intoxicated by psychopharmaceutical from the nursing thought was proposed.